Asymmetries in the Temporal Variation of the Electron Content During a Solar Eclipse - Meza, Amalia Margarita (2025)
Solar eclipses offer a unique opportunity to study rapid variations in the Earth´s atmosphere. Byaccurately modeling the timing and magnitude of obscuration caused by the Moon´s shadow, we can investigatethe eclipse´s impact on the behavior of the Earth´s ionosphere. Our approach involves deriving the vertical totalelectron content (VTEC) of the ionosphere using navigation satellite signals. Our previous research, conductedduring the 2017 North American eclipse, focused on a limited area. We employed a skewed Gaussian profile tomodel the temporal variation of the ΔVTEC curve, introducing a new parameter to better characterize the timedelay in the ionosphere´s response. This study broadens our research to include the East Coast and integrates theGlobal Ionosphere‐Thermosphere Model (GITM). The skewness parameter reflects the relative durations ofionospheric decay and recovery, where positive values indicate rapid decay coupled with slow recovery andnegative values suggest the opposite. Although our ΔVTEC simulation using GITM qualitatively matchesobserved behaviors, it faces challenges in accurately capturing the maximum drop and recovery phases,particularly in the eastern regions, likely due to insufficient consideration of plasmaspheric refilling, whichsignificantly influences the recovery of the upper ionospheric layers. The path of the eclipse totality delineates aboundary where positive asymmetries are observed to the south while negative asymmetries appear to the north.